Demoxepam Derivatization and GC–MS Analysis Produces Erroneous Nordiazepam and Oxazepam Results. Issue 5 (23rd February 2019) - Sarris, Gregory G; Limoges, Jennifer F
Abstract: Demoxepam, when derivatized by silylation and analyzed using gas chromatography-mass spectrometry (GC-MS), produces artifacts which are falsely identified as nordiazepam and oxazepam. Demoxepam was analyzed unextracted at various concentrations, using different derivatization procedures, and on different GC-MS systems. Oxazepam and nordiazepam were consistently identified in neat demoxepam samples, despite the changing variables. Under certain conditions, oxazepam was identified as low as 50 ng/mL derivatized demoxepam, and nordiazepam identified as low as 500 ng/mL derivatized demoxepam. The analysis of underivatized demoxepam resulted in nordiazepam detection at levels ≥2, 500 ng/mL, whereas oxazepam was not detectable at or below 10, 000 ng/mL demoxepam. Isolating the derivatization procedures and GC-MS analyses demonstrates that these processes are responsible for any degradation or rearrangement reactions which are taking place. Laboratories which follow similar procedures for benzodiazepine confirmations should consider these findings when interpreting analytical data from chlordiazepoxide cases.